Conductivity Enhancement of Graphene and Graphene Derivatives by Silver Nanoparticles - Apostolos Koutsioukis; Katerina Vrettos; Vassiliki Belessi; Vasilios Georgakilas (Applied Sciences, 2023)
In this article, a facile way for the doping of graphene and graphene derivatives with silver nanoparticles at different Ag ratios is described. Ag nanoparticles were formed directly on the surface of two different graphene substrates dispersed in dimethylformamide by the reduction of Ag cations with NaBH4. A few layered graphene nanosheets (FLG) produced from graphite and reduced graphene oxide functionalized with amino arylsulfonates (f-rGO) were used as substrates. The final graphene/Ag nanoparticle hybrid in the form of solid, dense spots showed enhanced electrical conductivity, which can be attributed to the formation of conductive interconnections between the 2D nanosheets. Importantly, electrical conductivities of 20 and 167 103 S m−1 were measured for the hybrids of f-rGO and FLG, respectively, with the higher Ag percentage without an annealing process. A representative hybrid f-rGO with Ag nanoparticles was used for the development of a highly conductive water-based gravure ink with excellent printing properties.